The debate on Athenian democracy in French political philosophy of the 70s and 80s of the 20th century - Sarrión Andaluz, José (Anales del Seminario de Historia de la Filosofía, 2021)
The latest book by José Luis Moreno Pestaña presents the Athenian democracy as interpreted by French authors during the 1970s and 80s, with special emphasis on Foucault, Castoriadis and Rancière. This work focuses on the participatory cultural model that, at the specific moment in history, managed to adjust in order to avoid the vices inherent in any assembly model. Moreover, this book pleads for the need to distribute knowledge and cultural wealth to be able to develop a democratic political system. It stresses the importance of motivation, of participation rather than frustration, which is one of the reasons for political apathy and which highlights the need for regulation to keep oligarchy in check.